Effects of Improper Mechanical Force on the Production of Sonic Hedgehog, RANKL, and IL-6 in Human Periodontal Ligament Cells In Vitro - Erika Yamashita; Shinichi Negishi; Jun Kikuta; Mami Shimizu; Hidenobu Senpuku (MDPI AG, 2024)
Improper mechanical stress may induce side effects during orthodontic treatment. If the roots and alveolar bones are extensively resorbed following excess mechanical stress, unplanned tooth mobility and inflammation can occur. Although multiple factors are believed to contribute to the development of side effects, the cause is still unknown. Sonic hedgehog (Shh), one of the hedgehog signals significantly associated with cell growth and cancer development, promotes osteoclast formation in the jawbone. Shh may be associated with root and bone resorptions during orthodontic treatment. In this study, we investigated the relationships between Shh, RANKL, and IL-6 in human periodontal ligament (hPDL) cells exposed to improper mechanical force. Weights were placed on hPDL cells and human gingival fibroblasts (HGFs) for an optimal orthodontic force group (1.0 g/cm2) and a heavy orthodontic force group (4.0 g/cm2). A group with no orthodontic force was used as a control group. Real-time PCR, SDS-PAGE, and Western blotting were performed to examine the effects of orthodontic forces on the expression of Shh, RANKL, and IL-6 at 2, 4, 6, 8, 12, and 24 h after the addition of pressure. The protein expression of Shh was not clearly induced by orthodontic forces of 1.0 and 4.0 g/cm2 compared with the control in HGFs and hPDL cells. In contrast, RANKL and IL-6 gene and protein expression was significantly induced by 1.0 and 4.0 g/cm2 in hPDL cells for forces lasting 6~24 h. However, neither protein was expressed in HGFs. RANKL and IL-6 expressions in response to orthodontic forces and in the control were clearly inhibited by Shh inhibitor RU-SKI 43. Shh did not directly link to RANKL and IL-6 for root and bone resorptions by orthodontic force but was associated with cell activities to be finally guided by the production of cytokines in hPDL cells.